Ekstraksi Daun Mimba (Azadirachta indica A. Juss) dengan Pelarut Etanol - Nur Muhammad Muaddib Ahlullah (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Mimba or Azadirachta Indica A juss, is a kind of plant that can be utilized as material of nature pesticide and medicine. Parts of the mimba plant that often be utilized are its seed and leaf. This research aims to find out the influence of extraction temperature and ratio of solvent to feed to the yield. The obtained concentration of the mimba leaf extract can be used to determine the mass transfer coefficient. The extraction process was performed using three neck flask with a mixer and ethanol 96% as a solvent. At the beginning, the mimba leafs with -30+80 mesh was feed into the flask that containing amount of solvent and an overhead stirrer with 350 rpm. Ratio of solvent to feed was varied as well as temperature. To study the influence of temperature, time for extraction process was limited of one hour. However, to observe the influence of ratio of solvent to feed, the process was running untill the mimba leaf extract was constant. Within the process, periodically the extract was drawn out. Finally, The extract was observed using a spectrometer. Based on the results, the extraction of mimba leaf at 70oC on the ratio of solvent to mimba leaf of 35 ml : 1gram will result mimba leaf extracted of 7,41% and mass transfer coefficient of 4,27.10-5 (g extract /minute.mm2)